1988
DOI: 10.3109/01485018808987081
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Semen Analysis and Hypoosmotic Swelling Test with Subsequent Pregnancies

Abstract: The hypoosmotic swelling (HOS) test was evaluated in 40 men whose wives had no apparent fertility factors. Only one of 29 men with normal semen parameters had a surbnormal HOS test, and that couple failed to conceive compared to 27 of 28 with normal HOS tests who did conceive. All five couples with husbands with subnormal semen parameters but with normal HOS tests achieved a pregnancy, but none of the three with abnormal HOS tests achieved a pregnancy. The results suggest that the HOS test might be of value in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…A decrease in the number of HOS-positive forms in the ejaculates of men with oligozoospermia, asthenozoospermia, and oligoasthenozoospermia compared with men with normozoospermia has been reported [23]. Positive correlation was also observed between HOS and the fertilizing ability of sperm [21,22,[24][25][26], however, others have not found a significant correlation between HOS and in vitro fertilization (IVF) outcome [27][28][29][30]. Thus, the clinical utility of the HOS test in assessment of sperm function is still debatable.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A decrease in the number of HOS-positive forms in the ejaculates of men with oligozoospermia, asthenozoospermia, and oligoasthenozoospermia compared with men with normozoospermia has been reported [23]. Positive correlation was also observed between HOS and the fertilizing ability of sperm [21,22,[24][25][26], however, others have not found a significant correlation between HOS and in vitro fertilization (IVF) outcome [27][28][29][30]. Thus, the clinical utility of the HOS test in assessment of sperm function is still debatable.…”
Section: Introductionmentioning
confidence: 80%
“…The HOS test can predict the fertilizing capacity of human spermatozoa [9,21,22]. A positive HOS test is an indicator of the functional integrity of the sperm membrane as judged by a swollen head and curled tail of spermatozoa when exposed to hypo-osmotic conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Langenbucher et al [35] reported that pregnancies occurred only with ejaculates that had 60% or more HOSpositive spermatozoa. Finally, Check et al [ 14,161 concluded that the results of the HOS test were significantly more reliable than the results of the standard spermiogram in being predictive of conception. These investigators found that no couple, regardless of the standard spermiogram, achieved a pregnancy when the HOS test was abnormal.…”
Section: Data From In Vivo Observationsmentioning
confidence: 99%
“…The latter interacts in many of the sperm's physiologic actions, e.g., capacitation, the acrosome reaction, and binding to the zona pellucida. Check et al [12] evaluated this test in a group of infertility patients in whom the female counterpart was diagnosed with an infertility factor that was presumed corrected. Only one of 29 men with normal semen parameters (according to WHO standards) had a subnormal HOS score and did not achieve a pregnancy; 27 of the 28 couples who conceived had HOS scores that were normal or gray-zone (Fig.…”
Section: Hypo-osmotic Swelling (Hos) Testmentioning
confidence: 99%